2014
DOI: 10.1179/1476830514y.0000000164
|View full text |Cite
|
Sign up to set email alerts
|

Vegans report less stress and anxiety than omnivores

Abstract: A strict plant-based diet does not appear to negatively impact mood, in fact, reduction of animal food intake may have mood benefits. The improved mood domains were not consistent with those found in other studies, which may be due to methodological differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 40 publications
9
76
1
5
Order By: Relevance
“…The finding that fish intake is protective against depression and that low serum vitamin B12 levels increase risk is interesting in light of the findings by Beezhold et al 37,38 that following a vegetarian diet is associated with healthy mood states given the lack of fish consumption by those adhering to this dietary pattern and that vegetarian vitamin B12 levels are lower than that of omnivores. 39 In one study by this group, the intake of both the omega-6 essential fatty acid linoleic acid and the omega-3 essential fatty acid alpha-linolenic acid was associated with better mood.…”
Section: Introductionmentioning
confidence: 93%
“…The finding that fish intake is protective against depression and that low serum vitamin B12 levels increase risk is interesting in light of the findings by Beezhold et al 37,38 that following a vegetarian diet is associated with healthy mood states given the lack of fish consumption by those adhering to this dietary pattern and that vegetarian vitamin B12 levels are lower than that of omnivores. 39 In one study by this group, the intake of both the omega-6 essential fatty acid linoleic acid and the omega-3 essential fatty acid alpha-linolenic acid was associated with better mood.…”
Section: Introductionmentioning
confidence: 93%
“…Vegetarians and vegans tend to be more liberal, altruistic, universalistic, and empathic; and both ethical and economic reasons as well as health aspects are for them more important motivations for choosing their diets when compared to omnivores [2,5,18,19,37,51,59]. Differences regarding morals/ethics have been shown between omnivores, partial vegetarians, vegetarians, and vegans: The further along people are in the vegetarian spectrum, the more important moral and health reasons seem to become for their choice of food [2].…”
Section: Discussionmentioning
confidence: 99%
“…A notable number of studies have examined sociopsychological differences between vegetarians and omnivores and suggest that vegetarians have higher levels of empathy, altruism, and well-being, and that they are more likely to endorse universalistic values [2,5,18,19,38,53,54,55,56,57,58,59,60,61]. Results of a recently published survey suggest that authoritarianism and social dominance are more frequent in carnivores compared to vegetarians and vegans, most distinctively among carnivorous men [62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…excluding animal-derived food, may be more or less prone to develop mood disturbances compared to those with omnivorous eating styles: large epidemiological studies (n = 6,422-90,380) showed higher depressive symptoms in vegetarians and vegans 1517 and in those with orthorexic behaviour 18 . Yet other (smaller) cross-sectional (n = 620) and interventional (n = 39-291) studies proposed a positive effect of plant-based diets on well-being and subclinical depression scores 1922 . Recently, it has been suggested that not meat-restriction per se, but the number of excluded food groups predicts higher depressive scores 17 .…”
Section: Introductionmentioning
confidence: 97%